AI Chatbots in Education: Challenges and Opportunities - Narius Farhad Davar; M. Ali Akber Dewan; Xiaokun Zhang (Information)
With the emergence of artificial intelligence (AI), machine-learning (ML), and chatbot technologies, the field of education has been transformed drastically. The latest advancements in AI chatbots (such as ChatGPT) have proven to offer several benefits for students and educators. However, these benefits also come with inherent challenges, that can impede students’ learning and create hurdles for educators. The study aims to explore the benefits and challenges of AI chatbots in educational settings, with the goal of identifying how they can address existing barriers to learning. The paper begins by outlining the historical evolution of chatbots along with key elements that encompass the architecture of an AI chatbot. The paper then delves into the challenges and limitations associated with the integration of AI chatbots into education. The research findings from this narrative review reveal several benefits of using AI chatbots in education. AI chatbots like ChatGPT can function as virtual tutoring assistants, fostering an adaptive learning environment by aiding students with various learning activities, such as learning programming languages and foreign languages, understanding complex concepts, assisting with research activities, and providing real-time feedback. Educators can leverage such chatbots to create course content, generate assessments, evaluate student performance, and utilize them for data analysis and research. However, this technology presents significant challenges concerning data security and privacy. Additionally, ethical concerns regarding academic integrity and reliance on technology are some of the key challenges. Ultimately, AI chatbots offer endless opportunities by fostering a dynamic and interactive learning environment. However, to help students and teachers maximize the potential of this robust technology, it is essential to understand the risks, benefits, and ethical use of AI chatbots in education.